Near-Fatal Air Gun Injury in a Child – Case Report - M. S. Siddiquea; A. N. Vadysinghe; K. B. Ekanayake; D. M. G. Fernando (Sri Lanka Journal of Medicine, 2022)
Introduction: Air guns are widely used for recreation and to protect crops from animals. It is a pneumatic weapon capable of inflicting serious life-threatening injuries. The authors present a case of a child subjected to a life-threatening pellet injury to the head due to discharge of an air gun while playing.